2010
DOI: 10.1016/j.fertnstert.2009.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Replete vitamin D stores predict reproductive success following in vitro fertilization

Abstract: Objective-Hypothesizing that levels of 25OH-D in body fluids are reflective of vitamin repletion status, we aimed to determine if 25OH-D levels in the follicular fluid (FF) of infertile women undergoing in vitro fertilization (IVF) demonstrate a relationship with IVF cycle parameters and outcome. Design-Prospective Cohort study Setting-Academic tertiary care center Patients-84 infertile women undergoing IVFInterventions-FF from follicles ≥14mm; serum (n=10) and FF levels of 25OH-D Main outcome measures-Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
232
5
26

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 327 publications
(284 citation statements)
references
References 21 publications
21
232
5
26
Order By: Relevance
“…The results of the regression revealed that vitamin D deficiency was independently associated with lower CP rates (OR 0.61, 95 % 0.39-0.95, p=0.030). Similar to the suggestions made by Ozkan et al [69], Polyzos et al postulate that this finding might be due to a deleterious effect on endometrial receptivity.…”
Section: Systematic Review On Effects Of Vitamin D On Art Outcomessupporting
confidence: 74%
See 3 more Smart Citations
“…The results of the regression revealed that vitamin D deficiency was independently associated with lower CP rates (OR 0.61, 95 % 0.39-0.95, p=0.030). Similar to the suggestions made by Ozkan et al [69], Polyzos et al postulate that this finding might be due to a deleterious effect on endometrial receptivity.…”
Section: Systematic Review On Effects Of Vitamin D On Art Outcomessupporting
confidence: 74%
“…Only eight of the 34 articles retrieved from PubMed met criteria (Fig. 2) [66][67][68][69][70][71][72][73]. Reference lists of chosen studies and narrative reviews were cross-referenced to find additional studies.…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Importance of vitamin D for reproductive success is well described, albeit mostly in non-human animal models [22]; data in humans are sparse. In a cross sectional study of infertile women undergoing IVF, we had previously identified significantly higher levels of 25-hydroxyvitamin D (25OHD), a metabolite that reliably reflects the overall vitamin D status, in the follicular fluid of women achieving clinical pregnancy following IVF [23]. While this latter observation was recently corroborated by others [24], including in donor egg recipients [25], data relating vitamin D status to IVF outcome remain far from unequivocal [26].…”
Section: Introductionmentioning
confidence: 94%